2021
DOI: 10.3390/insects12080743
|View full text |Cite
|
Sign up to set email alerts
|

Bombyx mori β-1,3-Glucan Recognition Protein 4 (BmβGRP4) Could Inhibit the Proliferation of B. mori Nucleopolyhedrovirus through Promoting Apoptosis

Abstract: β-1,3-glucan recognition proteins (βGRPs) as pattern recognition receptors (PRRs) play an important role in recognizing various pathogens and trigger complicated signaling pathways in insects. In this study, we identified a Bombyx mori β-1,3-glucan recognition protein gene named BmβGRP4, which showed differential expression, from a previous transcriptome database. The full-length cDNA sequence was 1244 bp, containing an open reading frame (ORF) of 1128 bp encoding 375 amino acids. BmβGRP4 was strongly expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Several molecules were identified to inhibit or promote the proliferation of BmNPV in the silkworm. , Here, we showed that the genes BmSBSPON , BmPallc , BmGART , and BmppyR , whose transcription was upregulated by BmNPV, promoted the proliferation of BmNPV, while BmCLIP3 and BmCCE-un1 , which were downregulated by BmNPV, inhibited it, suggesting a positive role of these transcriptional variations for viral proliferation in the fat body of P50 larvae. The functions of BmSBSPON and BmppyR , as well as their homologues, in animals still need to be investigated: here, they were both identified to be associated with viral proliferation for the first time.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Several molecules were identified to inhibit or promote the proliferation of BmNPV in the silkworm. , Here, we showed that the genes BmSBSPON , BmPallc , BmGART , and BmppyR , whose transcription was upregulated by BmNPV, promoted the proliferation of BmNPV, while BmCLIP3 and BmCCE-un1 , which were downregulated by BmNPV, inhibited it, suggesting a positive role of these transcriptional variations for viral proliferation in the fat body of P50 larvae. The functions of BmSBSPON and BmppyR , as well as their homologues, in animals still need to be investigated: here, they were both identified to be associated with viral proliferation for the first time.…”
Section: Discussionmentioning
confidence: 71%
“…mori serine protease, BmSINAL10, red fluorescent protein (RFP), BmTCP-1β protein, B. mori proteinase lipase member H-A, and BmβGRP4 . Notably, BmAtlastin-n enhances the resistance of silkworms to both BmNPV and Nosema bombycis .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, its transcript level significantly increased at 24 h after silkworms received BmNPV infection, while it was dramatically downregulated 48 h and 72 h after viral infection compared with the control group. Previous studies suggested that the expression level of B. mori βGRP4 dramatically decreased from 12 h to 72 h after BmNPV infection [ 25 ]. It was likely that more BmIML-2 were induced and were secreted to recognize the invading BmNPV within 24 h of infection, and BmNPV might suppress the host’s own immune defense mechanisms after 48 h to 72 h. We considered that BmIML-2 might respond to the BmNPV infection and possess multiple functions in regulating innate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the increased proliferation of BmNPV was observed after the knockdown of BmIML-2 via siRNA. Moreover, several other PRRs identified previously have also shown that up- or downregulation of these genes would significantly modulate the proliferation of BmNPV, such as BmβGRP4 [ 25 ] and BmPGRP2-2 [ 14 ]. Thus, we conceived that BmNPV, acting as a typical PPR, was provided with the effective capacity to inhibit the infection and replication of BmNPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation